Exploring the Factor Structure of Financial Capacity in Cognitively Normal and Impaired Older Adults. Issue 1 (1st January 2018) - Gerstenecker, Adam; Triebel, Kristen; Eakin, Amanda; Martin, Roy; Marson, Daniel
ABSTRACT: Objectives : To investigate the factor structure of financial capacity using a direct-performance measure of financial skills (The Financial Capacity Instrument [FCI]) as a proxy for the financial capacity construct. Methods : The study sample was composed of 440 older adults who represented the cognitive spectrum from normal cognitive aging to mild cognitive impairment (MCI) to mild dementia: 179 healthy older adults, 149 participants with MCI, and 112 participants with mild Alzheimer's dementia (AD). Results : Both Velicer's Minimum Average Partial test and Horn's parallel analysis supported a four-factor solution which accounted for 46% of variance. The four extracted factors were interpreted as: (1) Basic Monetary Knowledge and Calculation Skills, (2) Financial Judgment, (3) Financial Conceptual Knowledge, and (4) Financial Procedural Knowledge . Conclusions : The study findings represent an important first step in empirically articulating the financial capacity construct in aging. The four identified factors can guide both clinical practice and future instrument utilization and development. Clinical Implications : Cognitively impaired older adults with MCI and mild AD dementia are likely to show financial changes in one or more of the four identified financial factors. Clinicians working with older adults should routinely examine for potential changes in these four areas of financial function.